Response of lacustrine glacier dynamics to atmospheric forcing in the cordillera darwin - Langhamer, Lukas; Sauter, Tobias; Temme, Franziska; Werner, Niklas; Heinze, Florian; Arigony-Neto, Jorge; Gonzalez, Inti; Jaña, Ricardo; Schneider, Christoph (Journal of Glaciology, 2024)
Calving glaciers respond quickly to atmospheric variability through ice dynamic adjustment. Particularly, single weather extremes may cause changes in ice-flow velocity and terminus position. Occasionally, this can lead to substantial event-driven mass loss at the ice front. We examine changes in terminus position, ice-flow velocity, and calving flux at the grounded la-custrine Schiaparelli Glacier in the Cordillera Darwin using geo-referenced time-lapse camera images and remote sensing data (Sentinel-1) from 2015 to 2022. Lake-level records, lake discharge measurements, and a coupled energy and mass balance model provide insight into the subglacial water discharge. We use downscaled reanalysis data (ERA-5) to identify climate extremes and track land-falling atmospheric rivers to investigate the ice-dynamic response on possible atmospheric drivers.
CRIS-Team Scopus Importer:2024-02-16